Toplotna obremenitev Save dolvodno od Trbovelj - Širca, Andrej (Acta hydrotechnica, 2000)
Results of the study "Thermal load of the Sava River related to the construction of TET3", are presented, where influences of the existing and of the planned Trbovlje Thermal Power Plant (TET), of the Krško Nuclear Power Plant (NEK) and of the reservoirs of the future chain of hydro power plants on the Lower Sava River on the thermal state of the river were studied. A brief presentation of the introductory part of the study (an analysis of the existing data) is given first during the presentation, which is followed by a presentation of the results of the 1D and of the 3D models. The aim of the latter was to illustrate the share of each future reservoir and of the point pollution sources (TET, NEK) on the thermal state of the Sava River. A simplified description of reservoirs and of the NEK cooling system were applied, while the TET was accounted for with all available details
Keywords: akumulacije; Krško nuclear powerplant; matematično modeliranje; mathematical modelling; nuklearna elektrarna Krško; pretočne hidroelektrarne; reka Sava; reservoirs; run-of-river hydro powerplants; termoelektrarna Trbovlje; the Sava River; thermal load; toplotna obremenitev; Trbovlje thermal powerplant